Assessing accounting competency: Curriculum evaluation at SMK XYZ Bandung - Nabila Khairunnisa; Sri Diana Putri; Raden Ayu Intan Fithriya; Dafha Priatama (Curricula: Journal of Curriculum Development, 2025)
The rapid development of the business world demands competent human resources, especially in the field of accounting. This study describes the influence of the accounting curriculum and teaching methods on improving student competencies at SMK XYZ Bandung. By implementing the Kurikulum Merdeka, the school aims to create a responsive and adaptive learning environment. This research employs a qualitative descriptive approach involving interviews with two students, one accounting teacher, and curriculum representatives. The results indicate that the curriculum significantly impacts student motivation and engagement in learning. Additionally, the use of technology, such as Accurate, MYOB, and School.id applications enhance the effectiveness of accounting education. Despite challenges in teacher training and limited facilities, the implementation of a flexible curriculum allows teachers to be more creative in designing lessons. This study emphasizes the importance of investing in educational facilities and teacher training to improve the quality of education at SMK XYZ Bandung. The findings are expected to assist in evaluating the role of the curriculum and learning facilities in preparing students to face the increasingly competitive job market.   Abstrak Perkembangan dunia usaha yang semakin pesat menuntut adanya sumber daya manusia yang kompeten, terutama di bidang akuntansi. Penelitian ini menggambarkan pengaruh kurikulum dan metode pembelajaran akuntansi terhadap peningkatan kompetensi peserta didik di SMK XYZ Bandung. Dengan menerapkan Kurikulum Merdeka, sekolah ini berusaha menciptakan lingkungan belajar yang responsif dan adaptif. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan melibatkan wawancara dengan dua peserta didik, satu guru akuntansi, dan pihak kurikulum. Hasil penelitian menunjukkan bahwa kurikulum secara signifikan berdampak pada motivasi dan keterlibatan peserta didik dalam pembelajaran. Selain itu, penggunaan teknologi, seperti aplikasi Accurate, MYOB dan School.id, meningkatkan efektivitas pembelajaran akuntansi. Terlepas dari tantangan dalam pelatihan guru dan keterbatasan fasilitas, penerapan kurikulum yang fleksibel memungkinkan guru untuk lebih kreatif dalam merancang pembelajaran. Penelitian ini menekankan pentingnya investasi dalam fasilitas pendidikan dan pelatihan guru untuk meningkatkan kualitas pendidikan di SMK XYZ Bandung. Temuan ini diharapkan dapat membantu mengevaluasi peran kurikulum dan fasilitas pembelajaran dalam mempersiapkan peserta didik untuk menghadapi tantangan di dunia kerja yang semakin kompetitif. Kata Kunci: kompetensi peserta didik; Kurikulum Merdeka; motivasi belajar; pembelajaran akuntansi; teknologi pendidikan